2014
DOI: 10.1186/2193-1801-3-132
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of carotid artery stenting with two types of distal protection filter device

Abstract: PurposePreventing cerebral embolism from debris produced during carotid artery stenting (CAS) is important. This study compared the treatment outcomes of CAS using two types of filter-based embolic protection devices currently in use in Japan.Materials and methodsWe assessed 121 consecutive cases of CAS performed with FilterWire EZ™ between July 2010 and November 2012 and 37 consecutive cases of CAS performed with the Spider FX™ between November 2012 and June 2013. A Carotid Wallstent™ was used in all cases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Table 1 shows that when comparing CEA and CAS, the frequency of ICH in the context of CHS in large studies was higher after CAS, ranging from 0.28% to 4.05%. (1, 7,9,19,30,39,42,47,49,55,57,65) In CEA varied from 0% to 2.15%. (2,5,9,10,13,16,18,20,23,29,34,(43)(44)(45), 47, 61) Also, 73% of the studies involving CAS had a frequency of ICH in the context of CHS above 0.5%.…”
Section: 2-study Characteristicsmentioning
confidence: 98%
See 3 more Smart Citations
“…Table 1 shows that when comparing CEA and CAS, the frequency of ICH in the context of CHS in large studies was higher after CAS, ranging from 0.28% to 4.05%. (1, 7,9,19,30,39,42,47,49,55,57,65) In CEA varied from 0% to 2.15%. (2,5,9,10,13,16,18,20,23,29,34,(43)(44)(45), 47, 61) Also, 73% of the studies involving CAS had a frequency of ICH in the context of CHS above 0.5%.…”
Section: 2-study Characteristicsmentioning
confidence: 98%
“…(2,5,9,10,13,16,18,20,23,29,34,(43)(44)(45), 47, 61) Also, 73% of the studies involving CAS had a frequency of ICH in the context of CHS above 0.5%. (1, 7,9,19,30,39,42,47,49,55,57,65) In CEA, these frequencies occurred in only 26% of the cases. (2, 5, 9, 10, 13, 16, 18, 20, 23, 29, 34, 43-45, 47, 61) The "ICH to CHS proportion" has higher after CAS in comparison to CES: 7 out of 11 CAS studies (63.6%) had 50% or more hemorrhagic CHS (range 0-100%).…”
Section: 2-study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these devices may engage the vessel wall more firmly than concentric filter EPDs, thereby providing better protection from embolization; ICA flow impairment is caused occasionally in CAS performed using filter EPD. 13,14) Iko et al 15) and Roffi et al 14) reported that the incidence of flow impairment was lower in the Spider FX than in the other filter EPD groups. However, the difference was not statistically significant because the number of patients treated using the Spider FX was relatively small.…”
Section: Discussionmentioning
confidence: 97%